A Computer Security System for Cloud Computing Based on Encryption Technique - Aliu Daniel; Muyideen Omuya Momoh (Computer Engineering and Applications Journal, 2021)
In recent years, progressively data proprietors have embraced cloud storage service, by which they will subcontract their data to the cloud server to significantly reduce the local storage overhead, due to the rapid growth in the cloud computing market and development. Cloud computing is the delivery of hosting services that are provided to clients over the web. It is quite common, convenient, on-demand network access to a shared pool of configurable computing resources (e.g., networks, servers, storage, applications, and services) that may be rapidly provisioned and released with minimal management effort or service provider interaction. Sensitive information on the cloud is developing unexpectedly and bringing up several challenges and massive security concerns of the modern-day world. The cloud data and services reside in massively scalable data centers and may be accessed ubiquitously. Some issues concern in accessing this data is the security and confidentiality of consumer data in phrases of its location, relocation, availability, and security. Numerous users are surfing the Cloud for various purposes, therefore, they have highly safe and protracted services. The long run of the cloud, especially in expanding the range of applications, involves away the deeper degree of privacy, and authentication. Because of the safety concern associated with cloud computing, this paper presents a Computer Security System for Cloud Computing by employing a simple data protection model where data is encrypted using Advanced Encryption Standard (AES) technique before it is launched to the cloud, thus ensuring data confidentiality and security which is implemented with packet tracer.